Implementation of Website-Based Student Attendance System Using Codelgniter Framework at NU Ungaran Vocational High School - Hardiko, Nova Dwi; Rohman, Abdul (Universitas Bina Darma, 2024)
Nowadays, the use of technology is really needed by all levels of humans and education to make it easier to process data. The attendance information system at Vocational School NU Ungaran is currently still implemented conventionally or manually, such as the teacher taking the attendance data book in administration, then the teacher calls the students one by one for the process of filling in the attendance, then the teacher hands it over to the picket officer after finishing class time to be attended to. recap of attendance data, according to one of the teachers and picket officers, it was less efficient, which often resulted in damage or loss of the attendance book. The aim of this research is to make it easier for teachers and picket officers at Vocational School NU Ungaran when recording attendance data for all students. In this way the author designed my attendance using PHP and MySQL to process the database. My absence website is equipped with a QR code which is supported by using a camera or laptop camera which functions to take photos of students' barcodes for attendance. The results of this research aim to make it easier for teacher picket officers at Vocational School NU Ungaran to carry out attendance recaps.